Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Review: 128

Answer

$-i\sqrt 6$

Work Step by Step

$-\sqrt {-6}$ =$-\sqrt {-1\times6}$ =$-1\times\sqrt {-1}\times\sqrt {6}$ =$-1\times i\times\sqrt 6$ =$-i\sqrt 6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.